PENERAPAN LAJUR KHUSUS SEPEDA MOTOR PADA RUAS JALAN SEMARANG – KENDAL - Mahamarendra, Mustika; Medawati, Prestika Fiprilia; Riyanto, Bambang; Indriastuti, Amelia Kusuma (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Semarang - Kendal Road section is a connector between the central city of Semarang and Kendal. Traffic flows and accident rates through this street is quite high, especially accidents involving motorcycles. For that, the solution is the implementation of motorcycle lanes. From the analysis results DS in Siliwangi Road Sections is 0,75 and 0,78 in Walisongo Roads with low average speed is 27,58 km /h in Jalan Siliwangi. Analysis results obtained Siliwangi Road motorcycle accident is 70 % and 66 % on Walisongo Road. The proportion of motorcycle on Siliwangi road is 25.25 % - 41.66 % and 18.86 % - 41.43 % on Walisongo Road. Volume motorcycle in Siliwangi Road 1,687 pcu/hour and Walisongo Road 1,231 pcu/hour. Siliwangi Road DS is 0.75 and 0.78 on Walisongo Road. From solutions then selected by the best alternative with DS. Siliwangi road is divided into 4 segments, Segment I is to make the motorcycle lane with a width of 4 m and the other vehicle lane with a width of 8 m. Segment II is to make the motorcycle lane with a width of 4,25 m and the other vehicle lane with a width of 9,75 m. Segment III, this does not allow the roads to be made motorcycle lane because the road has a length of less than 100 m. Segment IV is to make the motorcycle lane with a width of 4 m and the other vehicle lane with a width of 7 m. In the Walisongo roads solution is to makes the motorcycle lane with a width of 4 m, and the other vehicle lane with a width of 7 m. Based on those motorcycle lanes parameters, can be concluded that the Semarang - Kendal Road section required motorcycle lanes with lane separators are markers.